Hungarian spa destinations in the tourism-oriented property market - Michalkó, Gábor; Rátz, Tamara (Hungarian Geographical Bulletin, 2010)
Hungary is ranked among the most important spa and health tourism destinations in the world. The number and variety of mineral and medicinal waters result in a unique supply in Eastern Central Europe. In Hungary, 51 settlements have certified medical spas, with Budapest, the capital city offering 7 medical spas alone. In addition to their favourable impact on tourism development, the wide range of baths and spa hotels of international standards also affect the real estate market in a positive way. Tourists, who wish to regularly benefit from the medicinal qualities of the waters and the associated medical treatments, may decrease their costs of stay either by buying their own property or by investing in a time-share accommodation facility. Of course, real estate transactions in spa destinations are not always explained by health tourism related motivations; buyers may plan to rent out their property and may be attracted by the expected return on their investment, or may simply wish to repeatedly enjoy the tourist milieu of a given destination. In this article, the spatial characteristics of Hungarian spa destinations’ domestic and international tourism demand will be analysed. In addition, the tourism-oriented characteristics of the spa towns’ housing markets (with special emphasis on second homes and other properties with leisure-related functions) are to be assessed and foreign citizens’ activities on the property market of these settlements evaluated. The research is based on the census and the tourism statistics of the Hungarian Central Statistical Office as well as the registry of foreigners’ real estate transactions drawn up by the Ministry of Local Government.